The curious incident of the dog in the night-time - Haddon, Mark 1962- (New York Doubleday, 2003)
Despite his overwhelming fear of interacting with people, Christopher, a mathematically-gifted, autistic, fifteen-year-old boy, decides to investigate the murder of a neighbor's dog and uncovers secret information about his mother.
UCWS-2922g donated by Patrick Valero - February 2016
Keywords: Autism -- Fiction; Savants (Savant syndrome) -- Fiction; England -- Fiction